2017
DOI: 10.1051/matecconf/201710101016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of uncoated and coated plastic waste coarse aggregates to concrete compressive strength

Abstract: Abstract. The use of plastic waste as coarse aggregates in concrete is part of efforts to reduce environmental pollution. In one hand the use of plastic as aggregates can provide lighter weight of the concrete than concrete using natural aggregates, but on the other hand bond between plastic coarse aggregates and hard matrix give low concrete compressive strength. Improvement of the bond between plastic coarse aggregate and hard matrix through a sand coating to plastic coarse aggregate whole surface is studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…However, a lack of information on the characteristics of lightweight concrete containing plastic aggregates is one of the main barriers hindering acceptance of this product in the construction industry. Polypropylene coarse aggregate, as shown in Figure 1, with or without sand coating, has been studied by Purnomo et al (2017a) and Pamudji et al (2018), who found a better bond between the coarse aggregate and hard matrix in the presence of the sand coating. Polypropylene has versatile physical characteristics and is inexpensive (Maddah, 2016;Jawaid and Khan, 2018); however, knowledge of the characteristics, strength, and stress and strain behaviors of lightweight concrete with plastic aggregate is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, a lack of information on the characteristics of lightweight concrete containing plastic aggregates is one of the main barriers hindering acceptance of this product in the construction industry. Polypropylene coarse aggregate, as shown in Figure 1, with or without sand coating, has been studied by Purnomo et al (2017a) and Pamudji et al (2018), who found a better bond between the coarse aggregate and hard matrix in the presence of the sand coating. Polypropylene has versatile physical characteristics and is inexpensive (Maddah, 2016;Jawaid and Khan, 2018); however, knowledge of the characteristics, strength, and stress and strain behaviors of lightweight concrete with plastic aggregate is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Research on low-density polyethylene LDPE plastic waste [7] and research on polyethylene plastic waste [8,9] as a substitute for fine aggregate in concrete have also been published. Other research works were on polycarbonate [10], and polypropylene (PP) wastes [11] as substitutes for coarse aggregate in concrete. Research on electronic plastic waste as a substitute for fine and coarse aggregates has also been carried out [12].…”
Section: Introductionmentioning
confidence: 99%
“…Some types of plastic previously used as aggregates in concrete mixtures include high density polyethylene (HDPE) [11], [12], polyethylene terephthalate (PET) [4], [9], [13]- [17], polyvinyl chloride (PVC) [18], [19], polypropylene (PP) [20], and electronic wastes (e-wastes) [21], [22].…”
Section: Introductionmentioning
confidence: 99%
“…To increase the interaction between cement paste and plastic aggregates to improve the mechanical performance of the concrete, Purnomo et al [20] coated the surface of the coarse aggregate PP developed by Pamudji el al [23] with volcanic sand, Choi et al [15] used raw materials from PET bottles waste and GBFS for making the lightweight aggregate, while Choi et al [4] used PET bottles waste and river sand powder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation